Determination of Saccharides in Honey Using Supercritical Fluid Chromatography Coupled with Single Quadrupole Mass Spectrometry. (1st September 2021) - Huang, Yang; Jiang, Zhengjin
Abstract: Saccharides are one of the most important biomoleculars in the world, which are responsible for various roles in living organisms. In this work, a combined use of mass spectrometry (MS) together with supercritical fluid chromatography (SFC) was applied for the separation of eight saccharides. A satisfactory separation was achieved within 15 min on a Unitary Diol column using 10 mM ammonium acetate in methanol as mobile phase additive at a temperature of 60°C. Compared to liquid chromatography–MS (LC–MS), the SFC–MS presented faster running time and better selectivity. The SFC–MS was validated and applied to the analysis of three saccharides (fructose, glucose and sucrose) present in different honey samples. The limits of detection (LODs) and limits of quantification (LOQs) of SFC–MS method for fructose, glucose and sucrose were 5.2, 4.5, 7.4 μg/mL and 17.2, 14.9, 24.1 μg/mL, respectively. The relative standard deviations for intrabatch and interbatch precision were <2.5% and the recoveries ranged from 97.6% to 103.1% for three concentration levels. The values of LODs and LOQs using SFC–MS method were lower (1.5–2.4-fold) than using LC–MS method. The results demonstrated the potential of SFC–MS for fast and sensitive determination of saccharides in honey.